Pelatihan Pembuatan Sabun Pembersih: Solusi Kemandirian Ekonomi bagi Ibu Rumah Tangga - Syam, Futri; Suriadi, Suriadi (Lok Seva: Journal of Contemporary Community Service, 2024)
This community service program aimed to enhance the economic independence of housewives through practical skills training in the production of liquid cleaning soap. The activity was conducted in Gattareng Village, Gantarang District, Bulukumba Regency, involving 24 participants. The implementation adopted the Participatory Rural Appraisal (PRA) method, emphasizing active community participation throughout the learning process. The training included theoretical sessions, interactive discussions, live demonstrations, and hands-on practice in soap making. Evaluation was carried out through pre- and post-tests to measure knowledge improvement, and a satisfaction questionnaire to assess participants’ responses. The results showed a significant increase in participants’ knowledge and skills: understanding of soap-making basics rose from 20% before training to 85% after the program. Moreover, 92% of participants stated that the training was highly beneficial, and 80% expressed willingness to produce liquid soap independently at home. Beyond improving technical capacity, the program fostered entrepreneurial motivation and strengthened solidarity among PKK (Family Welfare Movement) members. Economically, the training opened up new income opportunities since liquid soap is a household necessity with stable demand, easily accessible raw materials, and a simple production process. Therefore, this training serves as an effective model of women’s empowerment based on local skills, contributing to the enhancement of self-reliance and sustainable family economic welfare.